Role of physical therapists in providing care to older adults in welfare shelters during the hyper-acute phase of a disaster: lessons learned in Wajima City, Japan, after the 2024 Noto Peninsula earthquake - Abe, Toshiki; Saito, Hiroaki; Yamamoto, Chika; Eguchi, Yuichiro; Sato, Kei; Matsumoto, Misato; Hitachi, Kengo; Inoue, Sakiko; Zhao, Tianchen; Endo, Michioki; Sawano, Toyoaki; Ozaki, Akihiko; et al. (Frontiers in Disaster and Emergency Medicine, 2024)
Natural disasters pose significant challenges to affected communities, particularly vulnerable populations such as older adults. The aftermath of the Great East Japan Earthquake highlighted the necessity of welfare shelters to provide essential care. However, little is known about the specific role of physical therapists in these shelters. The aim of this article is to share the experiences and contributions of physical therapists in a welfare shelter in Wajima, Ishikawa Prefecture, immediately after the 2024 Noto Peninsula earthquake. The earthquake, with a magnitude of 7.6, damaged 76,589 houses, injured over 1,100 people, resulting in 245 deaths. The authors comprised a multidisciplinary team, including physical therapists, that provided short-term medical support at a welfare shelter in Wajima. Through several examples, we describe the contribution of physical therapists to evacuees’ health outcomes. Physical therapists played multifaceted roles in the welfare shelter, optimizing living environments, conducting physical screenings, and delivering continuous medical care, including respiratory care and exercise programs. The involvement of physical therapists in post-disaster evacuation shelters is crucial for enhancing emergency health care delivery and promoting community resilience.